## Step 1 :

Equation in ~ the finish of action 1 : ((0 - 3x2) - 12x) - 11 = 0

## Step 3 :

Pulling out like terms :3.1 traction out favor factors:-3x2 - 12x - 11=-1•(3x2 + 12x + 11)

Trying to factor by separating the center term

3.2Factoring 3x2 + 12x + 11 The first term is, 3x2 its coefficient is 3.The center term is, +12x its coefficient is 12.The last term, "the constant", is +11Step-1 : multiply the coefficient that the an initial term through the continuous 3•11=33Step-2 : discover two components of 33 whose sum equals the coefficient that the middle term, i beg your pardon is 12.

 -33 + -1 = -34 -11 + -3 = -14 -3 + -11 = -14 -1 + -33 = -34 1 + 33 = 34 3 + 11 = 14 11 + 3 = 14 33 + 1 = 34

Observation : No 2 such factors can be discovered !! Conclusion : Trinomial have the right to not it is in factored

Equation in ~ the finish of action 3 :

-3x2 - 12x - 11 = 0

## Step 4 :

Parabola, recognize the Vertex:4.1Find the peak ofy = -3x2-12x-11Parabolas have actually a greatest or a lowest point called the Vertex.Our parabola opens down and appropriately has a highest point (AKA absolute maximum). We understand this even before plotting "y" since the coefficient of the an initial term,-3, is negative (smaller 보다 zero).Each parabola has a vertical line of symmetry the passes with its vertex. Thus symmetry, the heat of the opposite would, because that example, pass with the midpoint of the two x-intercepts (roots or solutions) that the parabola. The is, if the parabola has actually indeed two genuine solutions.Parabolas have the right to model numerous real life situations, such as the height over ground, of things thrown upward, after ~ some duration of time. The peak of the parabola can administer us with information, such as the maximum elevation that object, thrown upwards, deserve to reach. For this reason we want to be able to find the coordinates of the vertex.For any kind of parabola,Ax2+Bx+C,the x-coordinate the the peak is offered by -B/(2A). In our instance the x coordinate is -2.0000Plugging into the parabola formula -2.0000 because that x we can calculate the y-coordinate:y = -3.0 * -2.00 * -2.00 - 12.0 * -2.00 - 11.0 or y = 1.000

Parabola, Graphing Vertex and also X-Intercepts :

Root plot for : y = -3x2-12x-11 Axis of symmetry (dashed) x=-2.00 Vertex in ~ x,y = -2.00, 1.00 x-Intercepts (Roots) : root 1 at x,y = -1.42, 0.00 source 2 at x,y = -2.58, 0.00

Solve Quadratic Equation by completing The Square

4.2Solving-3x2-12x-11 = 0 by completing The Square.Multiply both political parties of the equation by (-1) to acquire positive coefficient for the first term: 3x2+12x+11 = 0Divide both political parties of the equation by 3 to have 1 as the coefficient of the very first term :x2+4x+(11/3) = 0Subtract 11/3 indigenous both next of the equation :x2+4x = -11/3Now the clever bit: take it the coefficient of x, i beg your pardon is 4, divide by two, providing 2, and finally square it giving 4Add 4 come both sides of the equation :On the appropriate hand side us have:-11/3+4or, (-11/3)+(4/1)The usual denominator of the 2 fractions is 3Adding (-11/3)+(12/3) provides 1/3So adding to both political parties we ultimately get:x2+4x+4 = 1/3Adding 4 has completed the left hand side right into a perfect square :x2+4x+4=(x+2)•(x+2)=(x+2)2 things which are equal come the very same thing are likewise equal to one another. Sincex2+4x+4 = 1/3 andx2+4x+4 = (x+2)2 then, according to the legislation of transitivity,(x+2)2 = 1/3We"ll describe this Equation as Eq.

You are watching: What is the line of symmetry for the graph of y = -3x2 + 12x - 11?

See more: Harvest Moon Tale Of Two Towns Salad Recipe For The First Cooking Festival?

#4.2.1 The Square source Principle states that when two things are equal, their square roots are equal.Note the the square root of(x+2)2 is(x+2)2/2=(x+2)1=x+2Now, using the Square root Principle come Eq.#4.2.1 we get:x+2= √ 1/3 Subtract 2 from both sides to obtain:x = -2 + √ 1/3 since a square root has actually two values, one positive and the other negativex2 + 4x + (11/3) = 0has 2 solutions:x = -2 + √ 1/3 orx = -2 - √ 1/3 keep in mind that √ 1/3 can be created as√1 / √3which is 1 / √3 it is customary to further simplify until the denominator is radical free.This deserve to be achieved here by multiply both the nominator and also the denominator by√3Following this multiplication, the numeric worth of 1 /√3remains unchanged, as it is multiplyed by √3/√3 i beg your pardon equals1OK, let"s execute it:

1 • √3 1 • √3————————————— = ————————————√3 • √3 3